Синтез і властивості ніобійвмісного силікатного скла - Вахула, Я. І.; Зубачик, В. М.; Петришин, О. А.; Луцюк, І. В.; Тупісь, І. М.; Гавришкевич, Я. І.; Vakhula, Ya.; Zubachyk, V.; Petryshyn, O.; Lutsyuk, I.; Tupis, I.; Gavryshkevych, Ya. (Lviv Politechnic Publishing House, 2020)
Проаналізовано хімічні склади та властивості скла різних систем для виготовлення склоіономерних стоматологічних цементів (СІЦ). Для синтезу скла запропоновано базову систему 4SiO2–3Al2O3–xNb2O5–CaO із вмістом Nb2O5 8,8 та 16,2 % (мас.). Наведено високотемпературну технологію та параметри отримання скла для СІЦ. Визначено та проаналізовано властивості синтезованого ніобійвмісного скла. Методом диференційно-термічного аналізу встановлено вплив ніобію оксиду на кристалізаційну здатність скла.

The chemical compositions and properties of glass of different systems for the production of glass ionomer dental cements (GIC) were analyzed. For the synthesis of glass, the basic system 4SiO2–3Al2O3 – xNb2O5 – CaO with the content of Nb2O5 8.8 and 16.2 % (wt.) is proposed. High-temperature technology and parameters of glass production for GIC are presented in the article. The properties of synthesized niobiumcontaining glass were determined and analyzed. The effect of niobium oxide on the crystallization ability of glass was determined by the method of differential thermal analysis.
Synthesis and properties of niobium-containing silicate glass
Keywords: синтез скла; склоіономерний цемент; ніобійвмісне скло; властивості скла; термічний аналіз; synthesis of glass; niobium-containing glass; glass-ionomer cements; properties’ of glass; thermal analysis